A Study on Effectiveness of Elliott Wave Theory Forecasts for Precious Metals with Reference to Gold & Silver - Dharmaraj, C.; Balaji, G. (Indian Journal of Finance, 2011)
During the 1920-30's, there was an analyst named Ralph Nelson Elliott who came up with a theory called Elliott Wave Theory. Inspired by the Dow Theory and by observations found throughout nature, Elliott concluded that the movement of the stock market could be predicted by observing and identifying a repetitive pattern of waves, by applying this Elliott wave theory trader an investor could reduce risk and maximize profit. This theory will be effective when one learns this theory in depth. In applying the Elliott Wave Principle, the first task is to look at charts of market action and identify any completed five-wave and three-wave structures. Only then can we interpret where the market is and where it's likely to go. While applying the Elliott Wave Principle to any chart, we must keep in mind an important point that the Elliott Wave Principle does not provide certainty about any one market outcome. Elliott Wave analysis is a collection of complex techniques. Approximately 60 percent of these techniques are clear and easy to use. The other 40 are difficult to identify, especially for the beginner. The practical and conservative approach is to use the 60 percent that are clear. In this study, the researchers have used triangle pattern analysis and thrust wave analysis to predict the market of gold and silver.